Direct and sustained effects on leadership self-efficacy due to the inability to complete a parachute training course. Issue 3 (2nd July 2020) - Bergman, David; Gustafsson-Sendén, Marie; Berntson, Erik
Abstract: The present study examined a parachute training course intended to improve the leadership abilities of future military officers. Two research questions were examined. First, whether there were any differences between completers and non-completers in anxiety, stress, and collective identity at the beginning of the course (time 1), and second, whether there were any differences between completers and non-completers in leadership self-efficacy immediately after the course and at a five-month follow-up (time 2 and time 3). Participants were cadets from the Swedish Military Academy undergoing the course as part of their officer training curriculum. The results showed no significant differences between completers and non-completers in anxiety, stress, and collective identity at the beginning of the course (time 1). Non-completers showed a significant reduction in leader self-control efficacy compared to those who completed the training immediately after the course and at a five-month follow-up (time 2 and 3). Overall, these results indicate that non-completion of this type of demanding training could have negative effects on the individual's leader self-control efficacy.